2014
DOI: 10.5614/j.eng.technol.sci.2014.46.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Depositional Environment of the Sangkarewang Oil Shale, Ombilin Basin, Indonesia

Abstract: Abstract. Five samples from a 56 m long drill core that was recovered from the lacustrine Sangkarewang oil shale have been studied by means of petrography and organic geochemistry in order to investigate the organic matter composition and depositional environment of the shale. The organic matter consisted of abundant lamalginite (30%, v/v) and a very limited amount of vitrinite, suggesting an aquatic depositional environment with minor terrestrial influence. Organic geochemical analysis exhibited the dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The Sangkarewang oil shale is calcareous as reported by e.g. Koesoemadinata and Matasak (1981) with carbonate content in Talawi area is up to 55% (wt) (Anggayana et al, 2014). The mineralogy of Sangkarewang oil shale has been discussed in detail by Fatimah and Ward (2009).…”
Section: Indonesian Journal On Geoscience Geological Agency Ministry mentioning
confidence: 86%
See 3 more Smart Citations
“…The Sangkarewang oil shale is calcareous as reported by e.g. Koesoemadinata and Matasak (1981) with carbonate content in Talawi area is up to 55% (wt) (Anggayana et al, 2014). The mineralogy of Sangkarewang oil shale has been discussed in detail by Fatimah and Ward (2009).…”
Section: Indonesian Journal On Geoscience Geological Agency Ministry mentioning
confidence: 86%
“…Journal homepage: h p://ijog.bgl.esdm.go.id ISSN 2355-9314 (Print), e-ISSN 2355-9306 (Online) I J O G petrology (Fatimah and Ward, 2009;Widayat et al, 2013) and organic geochemistry (Anggayana et al, 2014;Widayat et al, 2013). With respect to the presence of organic matter in the oil shale, the authors have demonstrated the depositional environments responsible for the organic matter preservation.…”
Section: Indonesian Journal On Geoscience Geological Agency Ministry mentioning
confidence: 98%
See 2 more Smart Citations
“…Batubara merupakan salah satu batuan sedimen padat yang mudah terbakar dan terbentuk dari hasil rombakan tumbuhan pada masa lampau, berwarna coklat-hitam, mengalami proses perubahan fisika dan kimia yang mengakibatkan pengayaan pada kandungan karbon (Anggayana & Widayat, 2007). Peringkat batubara adalah posisi batubara pada peningkatan kandungan karbon dari lignit hingga antrasit dan pada umumnya akan berbanding lurus dengan kualitas batubara.…”
Section: Pendahuluanunclassified